A CONCEPTUAL PAPER ON THE EFFECTS OF TECHNOSTRESS ON JOB PERFORMANCE AMONG TEACHERS WITH MODERATING ROLE OF TOXIC LEADERSHIP - Mohamad Haniff Bin Mohd Yasin; Ahmad Syahmi Ahmad Fadzil; Muhammad Bin Majid (Journal of Islamic, Social, Economics and Development, 2022)
Almost every job sector in this world is depending on Information, Communication and Technology (ICT) including the academic sector. Similarly, the process of teaching, learning, research and administration using ICT are heavily utilized in the academic institution. Technology nowadays is continuously augmented in teaching and learning to enrich the learners. Despite of ICT having many advantages, it can also create Technostress among teachers when overused, lack of competency or fast-changing of ICT. Hence, technostress can significantly affect their job performance if not properly regulated. This study intends to highlight the gap or the grey area of Technostress on job performance with the moderating role of toxic leadership and boss phubbing among school teachers. The findings of this study show the proposed framework derived from past studies and anchored the framework through Transactional Theory of Stress. Additionally, the findings also highlighted the gap left by the recent research and presented relationships among the constructs. This research is hopeful to contribute to the body of knowledge in exploring more on the effects of technostress on the job performance among the school teachers. Moreover, this research can give more insight to relevant ministry in regulating and mitigating the potential effect of technostress.